Ultra-pH-Sensitive Small Molecule Probe Showing a Ratiometric Fluorescence Color Change - Cui, Junjie; Kim, Gayoung; Kim, Sehoon; Kwon, Ji Eon; Park, Soo Young (WILEY-V C H VERLAG GMBH, 2020)
We synthesized an amphiphilic small molecule 1 by attaching oligo(ethylene glycol) (OEG) and N,N-diethylamine (DEA) units to a fluorescent dicyanodistyrylbenzene (DCS) core. The molecule is fully soluble in aqueous solution at low pH (pH<4.3) by protonation of the DEA groups; but, above pH 4.3, it self-assembles to form nanoparticles due to increased hydrophobicity upon deprotonation, leading to a ratiometric fluorescence color change from green emission in the monomeric form (lambda(em,max)=538 nm) to red emission in the aggregated form (lambda(em,max)=646 nm). It should be noted that the ratio of emission intensities at 538 nm and 646 nm (R=I-538/I-646) changes drastically about 42-fold within a very narrow pH range of 4.3-4.6.
Keywords: INTRACELLULAR PH; RANGE; DESIGN; NANOFIBERS; VALUES; SENSOR; WATER